Qualitative Assessment of Adherence to Anti-Tuberculosis Medication Among Active Tuberculosis Patients - Pavithra GB; R. Prassanna Adithiyan; Charumathi B; Timsi Jain (Medsci Publications, 2022)
Background: Non- adherence is one of the major risk factors for the emergence of MDR and XDR TB. It is also one of the key factors responsible for treatment failure, disease relapse, prolonged infection and death. This study was conducted to explore the various factors contributing to non-adherence to the Anti-TB medication. Methods: A qualitative study was done on Adult Pulmonary and extra pulmonary TB patients who were in course of the treatment. A total of 20 patients were enrolled. Socio -demographic details and specific questions regarding TB were collected using a semi-structured questionnaire. In depth telephonic interviews were conducted among all participants. Results: The study participants comprised between 15 to 68 years of age with a mean age of 36 ±14.9years. Factors influencing non-adherence to medication were grouped under Patient, medication, Socio-economic and Health care related factors, Motive. Almost all patients reported more than one factor. Conclusion: Increasing the awareness of various TB services in the community may increase knowledge and improve attitude among the patients. Providing more information about the effects of medication may reduce the risk of being non adherent. TB anonymous groups can be organized for patients to discuss their challenges while on treatment.